Fetal Intrapericardial Teratomas: An Update - Yuan, Shi-Min (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Fetal intrapericardial teratomas are rare and benign cardiac tumors. By comprehensive literature retrieval of the pertinent articles published since 2000, 49 articles with 61 cases of intrapericadial teratomas were recruited into this study. The intrapericardial teratomas were found during pregnancy in 55 cases (fetal group), while the tumors were detected until neonatal period in 6 cases (neonatal group). In the fetal group, 15 cases were critical with fetal/neonatal respiratory distress or cardiac tamponade. Antenatal treatments including centesis, shunt placement, open fetal surgery and the ex utero intrapartum treatment were required in 24 (43.6%) fetal cases. Postnatal intubation was required in 19 cases with 18 of them having immediate intubation after birth. Postnatal tumor resection was performed in 41 (95.3%) cases. In neonatal group, 4 neonates had respiratory distress and/or cardiac tamponade. Neonatal intubation was required in 1 (16.7%) patient. Surgical tumor resection was performed in all 6 patients. A comparison between the fetal and neonatal groups revealed that the fetal group was associated with higher refractory effusions while the neonatal group had a higher incidence of respiratory distress. Although the all cause death rate was higher in the fetal group than in the neonatal (25.5 vs. 0%), but lack of a statistical significance. Antenatal treatments for fetal intrapericardial teratomas are feasible but carry higher risks in comparison to neonatal cases.
Keywords: Pericardial teratoma; fetal surgery; fetus; hydrops